2017
DOI: 10.26681/jote.2017.010104
|View full text |Cite
|
Sign up to set email alerts
|

National Survey to Identify Mental Health Topics in Entry-level OT and OTA Curricula: Implications for Occupational Therapy Education

Abstract: Mental health has been identified as a priority practice area for occupational therapy. However, recent research suggests that the number of occupational therapy practitioners working in mental health is declining. The purpose of this survey research study was to examine the extent to which occupational therapy (OT) and occupational therapy assistant (OTA) programs include mental health topics in their curricula. A link to an on-line survey was sent to program directors of OT and OTA programs in the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Occupational therapy interventions for schoolchildren with mental health conditions are often overlooked, as services traditionally are solicited to support children with physical health concerns (Chan et al, 2017;Leigers et al, 2016). Egan and Cahill (2017) suggested that occupational therapists can be regarded as valuable members of the school-based interprofessional team if other school-based professionals are educated about the therapists' training, skills, and scope of practice. Investigating perceptions of school-based occupational therapists on their pediatric mental health treatment preparedness and confidence provided valuable information to contribute to the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational therapy interventions for schoolchildren with mental health conditions are often overlooked, as services traditionally are solicited to support children with physical health concerns (Chan et al, 2017;Leigers et al, 2016). Egan and Cahill (2017) suggested that occupational therapists can be regarded as valuable members of the school-based interprofessional team if other school-based professionals are educated about the therapists' training, skills, and scope of practice. Investigating perceptions of school-based occupational therapists on their pediatric mental health treatment preparedness and confidence provided valuable information to contribute to the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, current occupational therapy curricula may need enhancement to best meet the needs of a future healthcare climate. For example, occupational therapy programs across the country are inconsistently teaching prevention and wellness, cultural issues, and mental health (Egan & Cahill, 2017;Hildenbrand & Lamb, 2013;Talero et al, 2015). The literature suggests that culturally responsive education has too heavy a Western perspective and mental health content lacks a specific mental health focus beyond the Accreditation Council for Occupational Therapy Education (ACOTE) standards (AOTA, 2018;Egan & Cahill, 2017;Talero et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, occupational therapy programs across the country are inconsistently teaching prevention and wellness, cultural issues, and mental health (Egan & Cahill, 2017;Hildenbrand & Lamb, 2013;Talero et al, 2015). The literature suggests that culturally responsive education has too heavy a Western perspective and mental health content lacks a specific mental health focus beyond the Accreditation Council for Occupational Therapy Education (ACOTE) standards (AOTA, 2018;Egan & Cahill, 2017;Talero et al, 2015). For instance, mental health has already become a diminished area of practice as other professionals, such as psychologists, nurses, and social workers, have assumed the life-skills and work domains and limited the areas where occupational therapists are recognized as mental health providers (Gutman, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations